Awake Intranasal Insulin Delivery Modifies Protein Complexes and Alters Memory, Anxiety, and Olfactory Behaviors - Marks, David R. (Society for Neuroscience, 2009)
The role of insulin pathways in olfaction is of significant interest with the widespread pathology of diabetes mellitus and its associated metabolic and neuronal comorbidities. The insulin receptor (IR) kinase is expressed at high levels in the olfactory bulb, in which it suppresses a dominant Shaker ion channel (Kv1.3) via tyrosine phosphorylation of critical N- and C-terminal residues. We optimized a 7 d intranasal insulin delivery (IND) in awake mice to ascertain the biochemical and behavioral effects of insulin to this brain region, given that nasal sprays for insulin have been marketed notwithstanding our knowledge of the role of Kv1.3 in olfaction, metabolism, and axon targeting. IND evoked robust phosphorylation of Kv1.3, as well as increased channel protein–protein interactions with IR and postsynaptic density 95. IND-treated mice had an increased short- and long-term object memory recognition, increased anxiolytic behavior, and an increased odor discrimination using an odor habituation protocol but only moderate change in odor threshold using a two-choice paradigm. Unlike Kv1.3 gene-targeted deletion that alters metabolism, adiposity, and axonal targeting to defined olfactory glomeruli, suppression of Kv1.3 via IND had no effect on body weight nor the size and number of M72 glomeruli or the route of its sensory axon projections. There was no evidence of altered expression of sensory neurons in the epithelium. In mice made prediabetic via diet-induced obesity, IND was no longer effective in increasing long-term object memory recognition nor increasing anxiolytic behavior, suggesting state dependency or a degree of insulin resistance related to these behaviors.